ATM Deficiency Accelerates DNA Damage, Telomere Erosion, and Premature T Cell Aging in HIV-Infected Individuals on Antiretroviral Therapy - Zhao, Juan; Nguyen, Lam Ngoc Thao; Nguyen, Lam Nhat; Dang, Xindi; Cao, Dechao; Khanal, Sushant; Schank, Madison; Thakuri, Bal Krishna Chand; Ogbu, Stella C.; Morrison, Zheng D.; Wu, Xiao Y.; Li, Zhengke; et al. (Frontiers in Immunology, 2019)
HIV infection leads to a phenomenon of inflammaging, in which chronic inflammation induces an immune aged phenotype, even in individuals on combined antiretroviral therapy (cART) with undetectable viremia. In this study, we investigated T cell homeostasis and telomeric DNA damage and repair machineries in cART-controlled HIV patients at risk for inflammaging. We found a significant depletion of CD4 T cells, which was inversely correlated with the cell apoptosis in virus-suppressed HIV subjects compared to age-matched healthy subjects (HS). In addition, HIV CD4 T cells were prone to DNA damage that extended to chromosome ends - telomeres, leading to accelerated telomere erosion - a hallmark of cell senescence. Mechanistically, the DNA double-strand break (DSB) sensors MRE11, RAD50, and NBS1 (MRN) remained intact, but both expression and activity of the DNA damage checkpoint kinase ataxia-telangiectasia mutated (ATM) and its downstream checkpoint kinase 2 (CHK2) were significantly suppressed in HIV CD4 T cells. Consistently, ATM/CHK2 activation, DNA repair, and cellular functions were also impaired in healthy CD4 T cells following ATM knockdown or exposure to the ATM inhibitor KU60019 in vitro, recapitulating the biological effects observed in HIV-derived CD4 T cells in vivo. Importantly, ectopic expression of ATM was essential and sufficient to reduce the DNA damage, apoptosis, and cellular dysfunction in HIV-derived CD4 T cells. These results demonstrate that failure of DSB repair due to ATM deficiency leads to increased DNA damage and renders CD4 T cells prone to senescence and apoptotic death, contributing to CD4 T cell depletion or dysfunction in cART-controlled, latent HIV infection.